Case report: Hypnic headache responds to agomelatine–a potential prophylactic treatment option - Xu, Sui-yi; Li, Ling; Sun, Wen-xiu; Shen, Jia-yu; Li, Chang-xin (Frontiers in Neurology, 2023)
Introduction Hypnic headache (HH) is a rare primary headache that is characterized by strict sleep-related attacks. However, the pathophysiology of HH remains unclear. The nocturnal nature of this activity suggests a hypothalamic involvement. The pathogenesis of HH may involve the brain structure that regulates circadian rhythms and is related to an imbalance between hormones, such as melatonin and serotonin. Currently, evidence-based medicine for HH pharmacotherapy is lacking. Acute and prophylactic treatment of HH is based on only a few case reports. Here, we report a case study in which agomelatine showed desirable responsiveness for the prophylactic treatment of HH for the first time. Case description We present the case of a 58-year-old woman with a 3-year history of nocturnal left temporal pain that awakened her during the wee hours. Brain magnetic resonance imaging did not reveal any midline structural abnormalities associated with circadian rhythms. Polysomnography revealed headache-related awakening at approximately 5:40 am, after the last rapid eye movement phase. No sleep apnea-hypopnea events were observed, without oxygen saturation or blood pressure abnormalities. The patient was prescribed agomelatine 25 mg at bedtime as a prophylactic treatment. In the following month, the frequency and severity of the headaches decreased by 80%. After 3 months, the patient’s headache completely resolved, and the medication was discontinued. Conclusion HH only occurs during sleep in the real world, leading to substantial sleep disturbances in older populations. Headache center neurologists need to focus on the prophylactic treatment of patients before bedtime to avoid nocturnal awakening. Agomelatine is a potential prophylactic treatment option for patients with HH.